Role of Dimensionality on Quantum Atkinson Engine Performance Based on the Potential Well Using Two Lowest Energy Levels under Equal Heat Leakage in Hot and Cold Reservoirs - Saputra, Yohanes Dwi; Romido, Verby; Sibarani, Nikita Renovich Burju; Apriwandi, Apriwandi; Friska, Vira; Rafitasari, Yeti; Zulfa, Zulfa (POSITRON, 2026)
This study theoretically investigates the influence of system dimensionality (1D, 2D, 3D) on the performance of a quantum Atkinson engine, a cycle consisting of two isentropic, one isochoric, and one isobaric stroke. This engine is modeled as a quantum analog of the classical ideal gas in a piston-cylinder, where the working fluid is a spinless particle confined in a one-, two-, or three-dimensional potential well, utilizing its two lowest energy states. In the absence of heat leakage, a fundamental decoupling is observed, as the compression ratio increases, thermal efficiency shows negligible variation across different dimensions, yet power output scales linearly with dimension. Under heat leakage, the lower-dimensional system is more efficient at low leakage, but proven to be more thermodynamically fragile, as its efficiency and reversibility degrade most rapidly as the leakage increases. A lower-dimensional system also consistently yields lower power output for a certain efficiency. This highlights a core nano-engine design consideration, balancing the high-power output of multi-dimensional systems against the thermal instability of lower dimensions.